Veno-venous ECMO as a platform to evaluate lung lavage and surfactant replacement therapy in an animal model of severe ARDS - Robert Qaqish; Yui Watanabe; Marcos Galasso; Cara Summers; A adil Ali; Mamoru Takahashi; Anajara Gazzalle; Mingyao Liu; Shaf Keshavjee; Marcelo Cypel; Lorenzo Del Sorbo (Intensive Care Medicine Experimental, 2020)
Abstract Background There are limited therapeutic options directed at the underlying pathological processes in acute respiratory distress syndrome (ARDS). Experimental therapeutic strategies have targeted the protective systems that become deranged in ARDS such as surfactant. Although results of surfactant replacement therapy (SRT) in ARDS have been mixed, questions remain incompletely answered regarding timing and dosing strategies of surfactant. Furthermore, there are only few truly clinically relevant ARDS models in the literature. The primary aim of our study was to create a clinically relevant, reproducible model of severe ARDS requiring extracorporeal membrane oxygenation (ECMO). Secondly, we sought to use this model as a platform to evaluate a bronchoscopic intervention that involved saline lavage and SRT. Methods Yorkshire pigs were tracheostomized and cannulated for veno-venous ECMO support, then subsequently given lung injury using gastric juice via bronchoscopy. Animals were randomized post-injury to either receive bronchoscopic saline lavage combined with SRT and recruitment maneuvers (treatment, n = 5) or recruitment maneuvers alone (control, n = 5) during ECMO. Results PaO2/FiO2 after aspiration injury was 62.6 ± 8 mmHg and 60.9 ± 9.6 mmHg in the control and treatment group, respectively (p = 0.95) satisfying criteria for severe ARDS. ECMO reversed the severe hypoxemia. After treatment with saline lavage and SRT during ECMO, lung physiologic and hemodynamic parameters were not significantly different between treatment and controls. Conclusions A clinically relevant severe ARDS pig model requiring ECMO was established. Bronchoscopic saline lavage and SRT during ECMO did not provide a significant physiologic benefit compared to controls.